Pentahelix Collaboration for MSME Entrepreneurship Ecosystem Development during National Santri Day - Gautama Sastra Waskita; Denny Rakhmad Widi Ashari; Samlatul Izzah; Desi Rahmawati; Andrean Permadi (ADI Pengabdian Kepada Masyarakat, 2026)
The development of local entrepreneurship ecosystems requires collaborative engagement among multiple stakeholders to address the challenges faced by micro, small, and medium enterprises (MSMEs), particularly in digital marketing, business networking, and community-based economic empowerment. However, socio-cultural public events in regional contexts are often implemented only as ceremonial activities and have not been optimally utilized as platforms for entrepreneurship activation and collaborative ecosystem development. This community service program aimed to strengthen the local entrepreneurship ecosystem through a Pentahelix-based public engagement model during the National Santri Day 2025 celebration in Tulungagung, Indonesia. The program employed a participatory community development approach involving academia, business actors, community organizations, government institutions, and media partners. Activities included entrepreneurship campaigns, MSME exhibitions, digital marketing socialization, branding assistance, and stakeholder networking during a public walking event attended by 2,000 participants. The results indicate that the program successfully increased MSME product exposure, improved participants’ understanding of collaborative entrepreneurship and digital marketing, strengthened stakeholder networking, and enhanced public engagement in local economic activities. The findings suggest that socio-cultural community events can function as sustainable entrepreneurial activation platforms when integrated with collaborative governance and ecosystem-based empowerment strategies.